2004
DOI: 10.1161/01.cir.0000124221.84399.48
|View full text |Cite
|
Sign up to set email alerts
|

Lower Loop Reentry as a Mechanism of Clockwise Right Atrial Flutter

Abstract: Background-Right atrial reentrant tachycardia resulting from lower loop reentry (LLR) around the inferior vena cava (IVC) has been described recently. However, all reported cases of LLR in the literature have negative flutter waves on the inferior surface ECG leads similar to that of counterclockwise typical atrial flutter around the tricuspid annulus (TA). Right atrial flutter with positive flutter waves in the inferior ECG leads has been assumed to rotate as a single reentrant activation wave front around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…On the other hand, as Zhang et al showed, 3D activation sequence mapping in patients with CCW LLR revealed an activation wavefront circulating around the IVC with evidence of slow conduction and wavefront collision on the septal side. 8) In our study, all patients with CW LLR had a collision of the wavefronts over the high RA. The higher collision site than that of the previous report could be explained by the conduction delay created by the RA incisional scar.…”
Section: Anatomical Involvement Of the Llr Circuitmentioning
confidence: 51%
See 2 more Smart Citations
“…On the other hand, as Zhang et al showed, 3D activation sequence mapping in patients with CCW LLR revealed an activation wavefront circulating around the IVC with evidence of slow conduction and wavefront collision on the septal side. 8) In our study, all patients with CW LLR had a collision of the wavefronts over the high RA. The higher collision site than that of the previous report could be explained by the conduction delay created by the RA incisional scar.…”
Section: Anatomical Involvement Of the Llr Circuitmentioning
confidence: 51%
“…In contrast, Zhang and Scheinman et al previously confirmed that the LLR circuit propagated CCW around the IVC (caudal view). 8) We assumed that the clockwise direction of conduction around IVC may have better conductivity than the CCW direction. Scar around lower posterior RA may contribute to the different direction of conductivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al also reported patients whose tachycardia on surface ECG was consistent with clockwise atrial flutter, and in whom they found figure-of-8 double-loop reentry around both the IVC and TA. 9) They hypothesized that the flutter circuit was determined by the Oginosawa Y Lower loop reentry after WPW surgery revolution or conduction times around the IVC and TA; i.e., a shorter revolution time around the IVC compared with that around the TA caused LLR, whereas a shorter revolution time around the TA caused typical AFL. Similar revolution times around the IVC and TA resulted in figure-of-8 double loop reentry.…”
Section: Discussionmentioning
confidence: 99%
“…The likely mechanism in this case appears to be conduction of the last counterclockwise flutter beat across the crista terminalis breaking into the midseptal area and activating the septum, upward and downward, a clockwise lower loop re-entry. 3,4 Manifest conduction of the last beat of counterclockwise flutter across the crista terminalis with minimal delay (255 versus 245 ms measured at the bipole RA 19,20) likely becomes possible because of the absence of a competing wavefront of activation after the development of unidirectional block in the cavotricuspid isthmus. The upward wavefront subsequently travels up to the high right atrium and then down the lateral wall of the right atrium.…”
Section: Reversal Of Flutter Activation During Ablation E69mentioning
confidence: 99%